Competitive marketing strategies to improve the positioning of the local “H Sports Bar” in Bahía de Caráquez - Lemoine Quintero, Frank Angel (2024)
Competitive marketing has become the most effective tool to achieve a better market share at the regional level. The objective of the study was to analyze the effectiveness of a competitive marketing strategy to improve the positioning of the H Sports Bar in Bahía de Caráquez. Under the quantitative context, the descriptive method was applied to develop a study that describes the facts based on the applied instruments. Among the most relevant results, they referred to taking into account bars as a source of entertainment, which can be seen with the objectivity with which bars are rated. Based on this, several strategies can be proposed to strengthen the image, and achieve the loyalty of potential clients. Among the strengths of H Sports bar are the market, loyalty and market segmentation, which is compared with another location to see what the strengths of each one are and thus improve the location. Therefore, the proposal was focused on the development of a website to strengthen the competitive positioning of the H Sports Bar in Bahía de Caráquez.